Crescite et multiplicamini: Iconographic Analysis of the Fuero Juzgo Illumination (Madrid, Biblioteca Nacional, Vitr. 17-10) - Arriola Jiménez, María (Eikón / Imago, 2023)
The unusual iconographic program of the Fuero Juzgo preserved in the National Library of Spain is made up of two unparalleled illuminations. The first represents the Blessing of the marriage of Adam and Eve; the second is an arbor consanguinitatis that starts from Jesse. In the present study we will delve into its theological meaning by tracing in patristic and iconographic tradition the link that unites both elements –Jesse and the tree of consanguinity– and, in turn, these with the blessing of the union of the first parents. This allows us to recognize the insistence of its creator on the sacramental character of marriage, the link of the images with the contemporary nuptial liturgy, as well as to explain the meaning of these religious images in this juridical manuscript.